Mecanorreceptores e terminações nervosas livres nas polias anelares dos tendões flexores da mão: um estudo por imunofluorescência e microscopia confocal a laser - Abreu, Sângelo André Ribeiro (2024)
The human hand holds great importance in human life, enabling the manipulation of objects, sensing information from the environment through touch, being connected to defense mechanisms and conveying visual information through gestures. Various anatomical structures are part of the hand's framework, including the annular pulleys. These play a crucial role in maintaining the alignment of flexor tendons to the bones, optimizing movement, reducing energy expenditure and increasing the efficiency of finger flexor mechanism. The annular pulleys are five in number and are often affected by diseases and injuries, particularly the first pulley, known as A1. They are fibrocartilaginous in nature, with their own vascularization and possibly free nerve endings (FNE) and mechanoreceptors (MCR) within their structures. This study aims to fill a gap in understanding the innervation of annular pulleys, thereby contributing to improvements in the treatment of diseases affecting flexor tendons, such as stenosing tenosynovitis (trigger finger), as well as enhancing classic surgical techniques in this region. To investigate the presence of mechanoreceptors and free nerve endings, twenty (20) A1 pulleys from the ring finger of the right hand were removed from twenty non-frozen cadavers, followed by removal of unnecessary adipose and fibrous tissues, cryosectioning and laser confocal microscopic analysis after indirect immunohistochemical labeling, using PGP 9.5 (protein gene product) as the primary antibody and Alexa Fluor 488 as the secondary antibody. The data were statistically analyzed using GraphPad Prism® software. After analysis, we identified that the pulleys had a mean length of 0.98 ± 0.14 cm, mean width of 0.78 ± 0.18 cm, and mean weight of 0.11 ± 0.10 g. Statistical analysis indicated a significant difference between pulley samples for the weight variable. There was a strong correlation between weight, length, and width of the pulleys. In some samples we found type I mechanoreceptors (Ruffini) and in all samples studied, free nerve endings (type IV) were evident, exhibiting various shapes and distinct lengths. Fibrocartilaginous connective tissue, vessels and free nerve endings were observed at the edges of the A1 pulleys. It is concluded that the annular pulleys designated as A1 of the 4th finger of the right hand have free nerve endings and, in some cases, type I mechanoreceptors, varying in size and preferably located at the medial and lateral insertions, close to the fibrocartilaginous region. These findings are important for understanding the pathophysiology of hand flexor tendon diseases and guiding treatments and improvements in surgical techniques, aiming to minimize functional and nociceptive damage during medical procedures on the pulleys